Reconstructing a Museum Business Model Through an Emic Perspective: A Case Study of The SBY–ANI Museum and Gallery - Kamhar Lakumani; Harianto Harianto; Yudha Heryawan Asnawi (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Museums play an important role in delivering inspiration, education, and cultural preservation. The SBY–ANI Museum and Gallery is the first private presidential museum in Indonesia, aimed at inspiring visitors through the life journey of the 6th President of the Republic of Indonesia. However, there are still challenges in increasing visitor numbers and conveying the values that are intended to be shared.Purpose: This study aims to reconstruct the Business Model Canvas (BMC) of an inspirational museum by integrating an emic perspective.Design/methodology/approach: This study was conducted at the SBY–ANI Museum and Gallery in Pacitan, East Java, from October 2024 to February 2025. It employed the BMC framework and an emic approach to evaluate and redesign the museum’s operational strategy. The emic perspective, gathered from five figures closely associated with President SBY as respondents, was integrated to develop an improved BMC that aligns more deeply with his values and legacy.Findings/Results: The study finds that the museum’s initial BMC requires adjustments in customer segmentation, key activities, and key partnerships. The museum initially targeted high school students, but data indicate that most visitors are kindergarten to junior high school students attending school edutourism programs. Additionally, the museum’s revenue still relies heavily on ticket sales, highlighting the need for diversification through partnerships, memberships, and sponsorships.Conclusion: Integrating BMC with an emic perspective results in a more relevant and sustainable business model. Strengthening marketing strategies and engagement with cultural communities, youth organizations, and educational institutions is essential to enhancing its appeal, encouraging repeat visits, and expanding its market reach.Originality/value (State of the art): This study demonstrates that the BMC, when reconstructed through the integration of an emic perspective, can address gaps in business management within the cultural education sector. This approach fills a strategic void in museum planning, which often suffers from misalignment between operational activities and the cultural values intended to be conveyed. However, empirical studies that integrate emic perspectives into formal business model frameworks in museum governance remain limited. Keywords: business model canvas, emic approach, museum strategy, educational tourism, operational strategy